Understanding Sustainable Livelihoods with a Framework Linking Livelihood Vulnerability and Resilience in the Semiarid Loess Plateau of China - Wenli Ye; Yin Wang; Xinjun Yang; Kongsen Wu (Land, 2022)
Regional climate is complicated and unpredictable in the context of global climate change. Farmers on the Loess Plateau, who rely on agriculture and natural resources for subsistence, are one of the groups feeling the early effects of climate change. Their vulnerability is determined by their degree of connection with the natural environment. Frequent droughts on the Loess Plateau have severely challenged farmers’ livelihoods, although some actions have been taken to adapt to these changes. To enable farmers to find sustainable livelihood strategies in challenging natural conditions, we established a research framework to link livelihood vulnerability and resilience and applied it to Jiaxian County, a specific research area in the Loess Plateau of China. To validate previous research, we studied the fluctuation trends of farmers’ livelihood vulnerability and livelihood resilience in the past 30 years and the interrelationships between these two trends and their influencing factors. The results are as follows: since 1990, livelihood vulnerability has been polarized; however, moderate vulnerability has always been dominant. Livelihood resilience shows a trend of continuous enhancement. The relationship between livelihood vulnerability and resilience is complex, and the direction of change between the two can be both similar and different. The topography, arable land conditions, soil quality, and irrigation conditions in different areas impact vulnerability and resilience, and the degree of impact is different in different periods. Farmers’ livelihood strategies depend on their cognitive decision making and livelihood assets, which are critical vulnerability and resilience factors. Most farmers in the study area have undergone significant livelihood strategy changes, while some maintain their original livelihood strategies. These findings provide policy implications for reducing vulnerability, enhancing resilience, and helping smallholder farmers find sustainable livelihood strategies to avoid poverty traps.